Physicians' preventive practices: more frequently performed for male patients and by female physicians - Raphaëlle Delpech; Géraldine Bloy; Henri Panjo; Hector Falcoff; Virginie Ringa; Laurent Rigal (BMC, 2020)
Abstract Background We sought to analyze gender differences in General Practitioners' (GP) preventive practices: variations according to the GP's and the patient's genders, separately and combined, and the homogeneity of GPs' practices according to gender. Methods Fifty-two general practitioners volunteered to participate in a cross-sectional study. A sample of 70 patients (stratified by gender) aged 40-70 years was randomly chosen from each GP's patient panel. Information extracted from the medical files was used to describe the GPs' preventive practices for each patient: measurements of weight, waist circumference, glucose, and cholesterol; inquiry and counseling about smoking, alcohol consumption, diet, and physical activity, and dates of cervical smears and mammographies. An aggregate preventive score was calculated to assess the percentage of these practices performed by each GP for patients overall and by gender. Mixed models were used to test for gender differences. Results Questionnaires were collected in 2008-2009 for 71% of the 3640 patients and analyzed in June 2017. Male patients and female GPs were associated with the most frequent performance of many types of preventive care. The aggregate preventive score was higher for male patients (OR = 1.60, 95% CI 1.47-1.75) and female GPs (OR = 1.35, 95% CI 1.05-1.73). There was no combined effect of the genders of the two protagonists. Female patients of male GPs appeared to receive preventive care least frequently and female GPs to deliver preventive care more consistently than their male colleagues. Conclusion Physicians need to be aware of these differences, for both patient gender and their own.